Observations on the practice and profession of modeling and simulation: A survey approach. (June 2018) - Padilla, Jose J; Diallo, Saikou Y; Lynch, Christopher J; Gore, Ross
This paper reports on a survey capturing modelers' perspectives of Modeling and Simulation (M&S). The survey was completed by a total of 283 respondents from the M&S community with 167 fully completed surveys and 151 respondents identified as model builders. Participants include people from government, academia, and industry in varied roles ranging from researchers to business developers. Respondents also represent a diverse educational background ranging from oceanography, social sciences, and engineering. The survey focuses on three dimensions namely: (a) models and simulations, (b) participants, and (c) how participants interact with models/simulations. We provide six observations from the data analysis: there is no dominating paradigm in M&S, the agent-based community is distinct from the discrete-event community, conceptual modeling is the art of M&S, simulation verification is mostly a trial and error activity, validate by all means necessary, and model accreditation is still too uncommon. A key finding from these observations is the identification of an over-reliance on informal methods for conceptualization and verification in M&S. We posit that this over-reliance on informal methods challenges model/simulation validity.